HAPTIC DEVICES FOR ADVANCED INTERACTION WITH MULTIMEDIA SYSTEMS - Silva, Bruno Miguel Lopes e (2022)
This project report describes the work carried out to design and evaluate new interfaces for media consumption in Smart TVs. The main goal is the study of the different technologies that can integrate a new generation of remote controls, and the development of prototypes (interfaces) that allow to connect all selected technologies in order to find a combination that improves the users quality of experience (QoE). Traditionally, the use of remote controls for television control uses only mechanical buttons to execute different tasks but, due to constant technological progress, an evolution is underway in the way users consume television content, moving from traditional passive visualization of contents to interactive forms. In this new interactive forms the user increasingly uses actions, adapts and interacts with multimedia content, services on demand and applications that support multiple users (games, social networks, etc). To keep up with these developments, it is necessary to add features to the conventional remote controls to enable a dynamic control, fast and accurate text input methods, and haptic feedback that is appropriate for the tasks that users need to perform. Two interfaces were developed integrating different haptic technologies that would provide the features mentioned above (dynamic control, text input methods, and haptic feedback). To assess the operation of the developed interfaces, tests were performed with different users to obtain objective and subjective classifications. The contribution of this work, was the integration of technologies that can improve the users QoE when using a Smart Tvs/Boxes and collecting users satisfaction levels regarding to the use of these technologies in remote controls. The tests show that despite the large number of different haptic effects users preferred one for each type of different technologies. Based on user rating, for the dynamic interaction case, one technology has proved to be preferred. In the case of text input/editing, among the various technologies, one of the technologies allows a fast text input with the highest level of user satisfaction.